2017
DOI: 10.1111/cas.13444
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of dual‐specificity phosphatase 4 enhances cell proliferation and invasiveness in colorectal carcinomas

Abstract: It is widely accepted that aberrant activation of the Wnt signaling pathway is responsible for the development of precursor lesions of colorectal cancer (CRC). However, the molecular mechanisms involved in the process of progression from these precursor lesions to invasive lesions of CRC are not fully understood. Recently, we reported that constitutive activation of MAPK accompanied by downregulation of dual‐specificity phosphatase 4 (DUSP4), a MAPK phosphatase, contributes to the progression of precursor lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…All of the drugs used reduced Wnt signaling in these tumor cells already at sublethal concentrations ( Figure S4B) and within 8 h after application ( Figures 2G, 2I, and S4C). In these cells, the effects of XAV939 and the other compounds were less pronounced on the b-catenin level compared to HEK293 cells (Li et al, 2015), most likely due to a mutation in the b-catenin itself in HCT116 (Ichimanda et al, 2018;Shikata et al, 2017). Similar results were obtained in another colon cancer line, DLD1, characterized by constitutively active Wnt signaling due to a truncation in adenomatous polyposis coli (APC) (Homfray et al, 1998;Kishida et al, 1998), concerning viability upon treatment ( Figure S4D), reduction of Wnt signaling (Figures S4E and S4G), ATP depletion ( Figure S4F), and endoplasmic reticulum stress ( Figure S4G).…”
Section: Figure 3 Mitochondrial Fitness Fine-tunes Wnt Signaling In mentioning
confidence: 88%
“…All of the drugs used reduced Wnt signaling in these tumor cells already at sublethal concentrations ( Figure S4B) and within 8 h after application ( Figures 2G, 2I, and S4C). In these cells, the effects of XAV939 and the other compounds were less pronounced on the b-catenin level compared to HEK293 cells (Li et al, 2015), most likely due to a mutation in the b-catenin itself in HCT116 (Ichimanda et al, 2018;Shikata et al, 2017). Similar results were obtained in another colon cancer line, DLD1, characterized by constitutively active Wnt signaling due to a truncation in adenomatous polyposis coli (APC) (Homfray et al, 1998;Kishida et al, 1998), concerning viability upon treatment ( Figure S4D), reduction of Wnt signaling (Figures S4E and S4G), ATP depletion ( Figure S4F), and endoplasmic reticulum stress ( Figure S4G).…”
Section: Figure 3 Mitochondrial Fitness Fine-tunes Wnt Signaling In mentioning
confidence: 88%
“…Ichimanda et al reported that colorectal cancer tissue showed a higher expression of DUSP4 than that in normal tissue. However, compared to the superficial region, DUSP4 expression decreased in the deep region of the tumor, and the activity of ERKs increased (26). Saigusa et al demonstrated that decreased DUSP4 expression in colorectal cancer was significantly correlated with tumor progression and distance metastasis (10).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DUSP4 overexpression in CRC cell lines produced upregulation of MAPK targets, such as EGR1, FOS, and MYC, and downregulation of the mismatch repair gene MSH2, all these effects leading to an increase in cell proliferation (Gröschl et al, 2013). In contrast, it has been more recently reported that the decrease in the expression of DUSP4 in CRC cell lines activated ERKs, causing cell proliferation and invasiveness (Ichimanda et al, 2018). Interestingly, DUSP4 overexpression in CRC cell lines decreases their sensitivity to doxorubicin, a drug used to treat CRC (Kang et al, 2017).…”
Section: Dual-specificity Mapk Phosphatasementioning
confidence: 99%